2018
DOI: 10.1021/acs.biochem.8b00645
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Basis of the Fast Dark Recovery of the Short LOV Protein DsLOV from Dinoroseobacter shibae

Abstract: Light, oxygen, voltage (LOV) proteins, a ubiquitously distributed class of photoreceptors, regulate a wide variety of light-dependent physiological responses. Because of their modular architecture, LOV domains, i.e., the sensory domains of LOV photoreceptors, have been widely used for the construction of optogenetic tools. We recently described the structure and function of a short LOV protein (DsLOV) from the marine phototropic bacterium Dinoroseobacter shibae, for which, in contrast to other LOV photorecepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 70 publications
2
21
0
Order By: Relevance
“…Such structural arrangement is seen in many PAS domain-containing photoreceptors including phytochromes 48 and sensor histidine kinases. 22 The N-terminal extensions in the A′α helix, which embed the LOV2 domain in a more native-like phototropin environment, apparently modulate the extent of the structural response in the Jα helix. This process might be used in phototropins to integrate the photoresponses of both LOV1 and LOV2 domains and also to transmit the signal to the downstream kinase domain.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Such structural arrangement is seen in many PAS domain-containing photoreceptors including phytochromes 48 and sensor histidine kinases. 22 The N-terminal extensions in the A′α helix, which embed the LOV2 domain in a more native-like phototropin environment, apparently modulate the extent of the structural response in the Jα helix. This process might be used in phototropins to integrate the photoresponses of both LOV1 and LOV2 domains and also to transmit the signal to the downstream kinase domain.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Earlier studies focused on the effects of mutating the conserved cysteine, which forms a covalent bond with the flavonoid cofactor during the photocycle, and some random mutations on flavin binding and photochemical reactivity [55,56]. Later studies probed the effects of mutations on other properties, particularly the absorption spectrum [47,50,57,58], photocycle lifetime [57,59], brightness of the cysteine-less variants [9,19,20,60], generation of radicals [15,61,62] and thermal stability [21][22][23]. Many of these mutations were rational, or could be rationalized after initial discovery, thus allowing one to apply the same principles to impart a different LOV domain with the desirable properties.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we present time-resolved IR experiments on the short LOV protein DsLOV from the photoheterotrophic marine α-protobacterium Dinoroseabacter shibae . The protein, which has no fused effector domain, was only recently described and characterized with regard to structure and function. , Strikingly, DsLOV exhibits unique characteristics opposed to other LOV photoreceptors as it was found to participate in the regulation of photopigment synthesis in the absence of blue light. To this end, the dark state is the physiologically relevant signaling state.…”
Section: Introductionmentioning
confidence: 99%
“…DsLOV exhibits an accelerated photocycle with a lifetime of the adduct state of τ = 9.6 s . DsLOV carries a methionine residue at position 49, , where isoleucine or leucine residues are found at this position in other LOV domains. Several studies have shown that the exchange of this residue strongly influences the lifetime of the adduct state of LOV proteins. ,, Replacement of M49 by serine in DsLOV produces a variant with a faster dark-state recovery in the absence of large structural alterations compared to the wild type .…”
Section: Introductionmentioning
confidence: 99%